GatoPointment: Cat Health Appointment System - OMAR, WAN AHMAD WAAFI YASIN; Abdul Jalil, Rozita (Applied Information Technology And Computer Science, 2026)
Managing veterinary appointments and cat health records is often challenging when done manually using paper forms or phone contact. This issues occurs at AnggunVet Batu Pahat’s veterinary clinic, leading to missed appointments, incomplete health records, and inefficient communication between pet owners and veterinary clinics. This project introduces a web-based appointment system named GatoPointment for AnggunVet Batu Pahat. The system is designed to help pet owners book appointments, view their cats' health details, and receive email for appointment confirmation or reminders for upcoming appointments. It also allows the veterinary clinic to manage their schedules efficiently and access shared health record details for pet owners. The system will be developed using PHP, MySQL, and HTML/CSS, with email notifications powered by PHPMailer to inform users about appointment approvals and upcoming appointment reminders. The project followed a structured design and testing process to ensure the system is easy to use and reliable. Future improvements could include adding a mobile app or advanced features like automatic health tracking to make the system even more helpful for users and the clinic.